Medications for Opioid Use Disorder in the Criminal/Legal System: Knowledge, Beliefs, and Attitudes Among Rural Community-Based Stakeholders - Victor, Grant (Journal of drug issues, 2022)
The aim of this study was to describe rural community stakeholders’ attitudes and perceptions of providing medication for opioid use disorder (MOUD) to individuals in the criminal/legal system. Data were utilized from a technical assistance initiative aimed at strengthening community-based OUD treatment within criminal/legal systems. A mixed-methods approach was applied. Survey responses were used to compare stakeholders’ who had and had not attended an MOUD training, and semistructured interviews were conducted with a convenience sample of rural criminal/legal and treatment stakeholders. MOUD training was associated with endorsing the effectiveness of methadone, oral naltrexone, and injectable naltrexone. Three primary themes emerged from the stakeholder interviews: 1) acceptance of MOUD uptake; 2) stigma of MOUD and diversion concerns; and 3) gaps in MOUD treatment. Most interviewees noted that there is a scarcity of treatment options in their community, and among the existing services, there are considerable barriers to care.